PENGARUH BUZZ MARKETING DAN BRAND AWARENESS TERHADAP MINAT BELI PRODUK ERHA 21 (Studi pada forum online Female Daily Network) - Ramadila, Nabilla; Hussein, Ananda Sabil (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
In this global era, customers don’t buy company’s promise and usual advertising. They need something new, creative and more personal. Talk about a particular brand’s performance from trusted people are more influential than standard advertising. Thus made a new marketing concept named buzz marketing, based on the sound of something so noisy like thousand bees buzzing. This buzz more likely comes from some trusted references like friends, family, public figure, or any talks which come from trusted people. One of the media is online forum where people share the same interests and talk about it, just like in Female Daily Network where many Indonesian females meet virtually and talk about beauty, fashion and everything related to women life. Main interest of women’s world is mostly beauty which can’t be separated from beauty and aesthetic clinic, such as Erha 21 which is one of the most famous clinic in Indonesia. This study aims to determine the influence of buzz marketing and brand awareness toward customers’ intention to buy Erha 21’s product simultaneously and finds which one is the most influential variable. The number of respondents are 100 active member on Female Daily whose posted at least once at Erha 21’s thread. Research instrument used was questionnaire with purposive sampling technique. The analytical method used is multiple linear regression. Based on the results of the analysis, the variables brand awareness and buzz marketing have significantly influenced customers’ intetion to buy. Meanwhile, only brand awareness has a significant effect on brand trust. The variable brand awareness effects intention to buy dominantly. This study showed that buzz marketing and brand awareness influence intention to buy. Keywords : buzz marketing, brand awareness, purchase intention